The performance evaluation of AODV-based and DSR-based multi-radio routing protocols in cognitive radio Ad Hoc network - Che-Aron, Zamree; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran (Maxwell Scientific Organization, 2013)
Due to the huge advancement of wireless technologies, the radio spectrum is one of the most heavily used and costly natural resources. Cognitive Radio (CR) is a promising technology to solve the problem of radio spectrum shortage and spectrum underutilization by enabling unlicensed users to opportunistically access the available licensed bands in an intelligent and cautious manner. In Cognitive Radio Ad Hoc Networks (CRAHNs), which operate without centralized administration, the data routing is one of the most important issues to be taken into account and requires more study. In this study, we analyze and evaluate the performance of AODV-based and DSR-based multi-radio routing protocols (AODV-MR, extended DSR and MR-LQSR) in CRAHN using simulations in NS-2. The metrics used for performance analysis are average throughput, average end-to-end delay and average jitter. From the simulation results, it is observed that the MR-LQSR protocol provides better performance in term of average throughput and gives smallest number of dropped packets. Whereas the extended DSR gives better results of average end-to-end delay and average jitter.